2013
DOI: 10.1007/s11769-013-0625-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatially different nutrient histories recorded by multiple cores and implications for management in Taihu Lake, eastern China

Abstract: The Taihu Lake, a large shallow lake in the floodplain of the Changjiang (Yangtze) River in the eastern China, is faced with challenging ecological problems resulting from eutrophication, which has affected the regional freshwater supply of a large population. Although efforts have been made to assess the nutrient evolution histories in the northern bays, little is known regarding nutrient histories in different parts across the entire lake basin. In this paper, we present nutrient histories for different part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…SCP concentration maxima in this study are similar to those observed in other Yangtze floodplain sites, such as the Jianghan Plain (4000-15000 grains g -1 ; Boyle et al, 1999), Taihu Lake (600-9000 grains g -1 ; Cao et al, 2013;Rose et al, 2004),…”
Section: Scp Profilessupporting
confidence: 88%
“…SCP concentration maxima in this study are similar to those observed in other Yangtze floodplain sites, such as the Jianghan Plain (4000-15000 grains g -1 ; Boyle et al, 1999), Taihu Lake (600-9000 grains g -1 ; Cao et al, 2013;Rose et al, 2004),…”
Section: Scp Profilessupporting
confidence: 88%